Do parent mental illness and family living arrangement moderate the effects of the Aussie Optimism Program on depression and anxiety in children? - Cheng, Maryanne; Rooney, Rosanna; Kane, Robert; Hassan, Sharinaz; Baughman, Natalie (2018)
© 2018 Cheng, Rooney, Kane, Hassan and Baughman. Parent mental illness and family living arrangement are associated with depression and anxiety in children, and may influence the effects of programs that aim to prevent these disorders. This study investigated whether these family context factors moderated the intervention effects of the enhanced Aussie Optimism Positive Thinking Skills program on depression and anxiety in primary school children. The intervention was a universal, cognitive-behavioral program, with a one hour session each week for 10 weeks, delivered by trained teachers. The participants were 502 children from 13 private schools, aged 9-11, with 347 in the intervention group and 155 in the control group. There were 267 females and 235 males. Data from 502 parents was also included. A cluster randomized controlled trial design was used, including eight intervention schools and five control schools. Depression and anxiety were assessed at pre-test, post-test, and 6-months follow-up. Information on parent mental illness and family living arrangement was collected through a parent questionnaire. The data was analyzed using covariance analysis with Generalized Linear Mixed Methods. At baseline, depressive and anxiety symptoms did not differ significantly based on parent mental illness. Symptoms of depression at baseline were significantly higher for children from a higher-risk family living arrangement, but anxiety symptoms were not. Parent mental illness and family living arrangement did not moderate the effects of the program on depression and anxiety at post-test or 6-months follow-up. Parent mental illness moderated the intervention effects on negative self-esteem, an aspect of depression, at post-test, with improvements seen only for children who did not have a parent with a mental illness. The findings indicate an association between family living arrangement and depressive symptoms in children. The findings suggest that the program is effective for children regardless of parent mental illness or family living arrangement, although parent mental illness has the capacity to influence the program's outcomes.